PENGARUH LATIHAN RENANG TERHADAP KADAR HORMON KORTISOL PADA PENDERITA ASMA - Rahmaya Nova Handayani; Denny Agustiningsih; Achmad Djuneadi (Viva Medika, 2014)
Bronchial asthma is one of allergic disease and a health problem both in developedcountries and in developing countries characterized by reversible narrowing of the bronchi due tobronchial hyperactivity . The prevalence and hospitalization rates of bronchial asthma indeveloped countries from year to year tend to increase. One of the triggers of asthma is stress.Stress is closely related to a hormone called glucocorticoids . Glucocorticoids which regulatesmetabolism and resistance to stress , including cortisol , corticosterone and cortisone .Glucocorticoids can potentially respond kotekolamin the bronchial tissue , occurs only atconcentrations influence physiology . This suggests cortisol has a role in affecting airway tone in individuals.The purpose of this study was mengidentifikasipengaruh swimming against cortisol levels in patients with asthmaThe design of this study is a quasi experimental study with pre-post study design -test group design . Measurement of cortisol levels do in the beginning , middle and end of thetreatment pool exercises were performed 1 week 3 times in the morning with a sample of 20respondents . Cortsisol hormonal measurements done using ELIZA measurement , the blood of therespondents were taken before and after swimming practice . People with asthma are taken by amedical diagnosis is determined by the doctor at the health center Brits with the male genderThe result of this research is there before and after the effect of swimming exercise on cortisollevels in patients with asthma . Keywords : Pool , cortisol , asthma